Question #bf43b

3 Answers
Dec 12, 2017

6 2/3

Explanation:

Let's start by making these into improper fractions:

4 1/6 = 25/6

-2 1/2 = -5/2

After that we can properly subtract them, as such:

25/6 - (-5/2)
25/6 + 5/2
25/6+15/6 (Make the denominators the same number)
40/6 = 6 2/3

Hope this helps!

Dec 12, 2017

6 2/3

Explanation:

When you subtract change the sign of the number to be subtracted and add.
Before doing it change the numbers to full fraction
So we have
4 1/6 = 25/6
2 1/2 = 5/2
Now add them
25/6 + 5/2 = 25/6 + 15/6 = 40/6
Now simplify the fraction
40/6 = 20/3 = 6 2/3

Dec 12, 2017

6 2/3

Explanation:

If you look at a graphical number line, you can see that the negative of a negative number is just the "positive" (it just switches the direction along the line).

4 1/6 - -2 1/2 = 4 1/6 + 2 1/2
From here we just need to express both fractions with equal denominators. 2 is a factor of 6, so we will use 6.
4 1/6 + 2 1/2 = 4 1/6 + 2 3/6 = 6 4/6 or 6 2/3